2011
DOI: 10.1007/s10778-011-0478-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the shock load on an electroelastic bimorph disk

Abstract: A numerical-analytic method for the identification of the axisymmetric mechanical shock load on a disk-shaped metal-piezoceramic bimorph transducer is proposed. A problem is formulated based on the theory of thin two-layer plates. The solution is found using the Laplace transform. By recovering the original function analytically, the problem is reduced to a system of Volterra equations, solved numerically using Tikhonov's regularization algorithm. The finite-element solution of the direct problem is used as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Reference [31] demonstrated that the Tikhonov regularization method can solve the inverse problem in a stable manner despite the presence of noisy data. Reference [32] identified the shock load on an electroelastic bimorph disk using the Tikhonov regularization method. However, the Tikhonov regularization method is not completely perfect; there are numerous unavoidable limitations and disadvantages, which is described as follows: (a) the approximate solution provided by Tikhonov regularization method is too smooth; (b) the approximate solution provided by Tikhonov regularization method may lack some details that the desired real solution might possess.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Reference [31] demonstrated that the Tikhonov regularization method can solve the inverse problem in a stable manner despite the presence of noisy data. Reference [32] identified the shock load on an electroelastic bimorph disk using the Tikhonov regularization method. However, the Tikhonov regularization method is not completely perfect; there are numerous unavoidable limitations and disadvantages, which is described as follows: (a) the approximate solution provided by Tikhonov regularization method is too smooth; (b) the approximate solution provided by Tikhonov regularization method may lack some details that the desired real solution might possess.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%